Effects of patients’ anxiety, previous pain experience and non‐drug interventions on the pain experience during colonoscopy - Ylinen, Eeva‐Riitta; Vehviläinen‐Julkunen, Katri; Pietilä, Anna‐Maija (Journal of Clinical Nursing, 2009)
Aims. This paper is a report of a study evaluating anxiety in patients prior to colonoscopy and identifying correlations between that anxiety, previous pain experience, non‐drug interventions and pain intensity during colonoscopy. Background. Waiting for forthcoming procedures, such as colonoscopy, is stressful. However, a few studies have evaluated the influence of patients’ anxiety, previous pain experience and non‐drug interventions during colonoscopy. Design. A quantitative cross‐sectional survey design was used. The data were collected from colonoscopy patients by using the Spielberger State Trait Anxiety Inventory and a questionnaire developed for the study. Methods. We assigned one hundred and thirty patients scheduled for diagnostic colonoscopy in a Finnish university hospital during 2006. Patients completed the State Trait Anxiety Inventory before and a questionnaire developed for the study after colonoscopy. Results. Most of the patients suffered from pain but they considered it to be tolerable. Women were more anxious before colonoscopy and experienced more pain and discomfort than men. Previous pain experiences and high state anxiety level decreased patients’ perceptions of colonoscopy. Non‐drug interventions, such as peaceful talk, explanation of the reason for pain and guidance helped both anxious and non‐anxious patients to ease the pain. Conclusion. Awareness and understanding of previous pain experiences and anxiety levels in patients are essential and must be taken into account. Relevance to clinical practice. Colonoscopy patients’ clinical education should be developed so as to be more individual. Furthermore, nurses should be better aware of the positive effects of non‐drug interventions and should use them as an element of pain management for colonoscopy patients.